Identity of the millipede genus Pyrgodesmus Pocock, 1892, the type genus of the family Pyrgodesmidae (Diplopoda, Polydesmida) - Golovatch, Sergei I. (Zootaxa, 2021)
Revision of Pyrgodesmus obscurus Pocock, 1892, the only, and type species of Pyrgodesmus Pocock, 1892, shows that the genus currently includes two species, P. obscurus and P. permutatus (Attems, 1936), comb. nov. ex Klimakodesmus Carl, 1932. Both species are properly illustrated and both seem to be endemic to Sri Lanka. Pyrgodesmus is rediagnosed viz-à-viz the presumably especially similar and likewise oligotypic genus Klimakodesmus from southern India.